2005
DOI: 10.1124/dmd.104.001883
|View full text |Cite
|
Sign up to set email alerts
|

Species- And Disposition Model-Dependent Metabolism of Raloxifene in Gut and Liver: Role of Ugt1a10

Abstract: ABSTRACT:Caco-2 cell lysate, and intestinal and liver microsomes derived from female humans and rats were used to compare and contrast the metabolism and disposition of raloxifene. In Caco-2 cell lysate, raloxifene 6-␤-glucuronide (M1) was the main metabolite, although raloxifene 4-␤-glucuronide (M2) was formed in comparable abundance (58% versus 42%). In rat liver and intestinal microsomes, M1 represented about 76 to 86% of glucuronidated metabolites. In contrast, raloxifene 4-␤-glucuronide (M2) was the predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 36 publications
5
99
1
Order By: Relevance
“…Only about 2% of administered raloxifene is bioavailable [1] but despite this, the drug is known to have a long biological half life of 27 hr. The reason for this disparity is that raloxifene is a polyphenolic drug that can be glucuronidated and sulfated by bacteria in the gut so the drug cannot be absorbed [107,108]. This phase II metabolism in turn controls enterohepatic recirculation and ultimately impairs the drug from reaching and interacting with receptors in the target.…”
Section: Metabolic Mimicrymentioning
confidence: 99%
“…Only about 2% of administered raloxifene is bioavailable [1] but despite this, the drug is known to have a long biological half life of 27 hr. The reason for this disparity is that raloxifene is a polyphenolic drug that can be glucuronidated and sulfated by bacteria in the gut so the drug cannot be absorbed [107,108]. This phase II metabolism in turn controls enterohepatic recirculation and ultimately impairs the drug from reaching and interacting with receptors in the target.…”
Section: Metabolic Mimicrymentioning
confidence: 99%
“…The role of intestinal first-pass glucuronidation may be significant, however, especially if the drug is a substrate to an extrahepatically expressed UGT isoform, such as UGT1A10, and if glucuronidation is an important metabolic route for the given compound. Raloxifene may be an interesting example in this respect (Jeong et al, 2005).…”
Section: Fig 3 Kinetics Of S-(oe)mentioning
confidence: 99%
“…According to the estimations, the fraction of raloxifene absorbed is high, 60 %, but only 2% reaches the systemic circulation in unconjugated form due to the high metabolic turnover during absorption [7]. The rest represents raloxifene conjugated by UDP-glucuronosyltransferases (UGTs) to raloxifene-4'-β-glucuronide (M2), raloxifene-6-β-glucuronide (M1) [7,8] and raloxifene-6,4'-diglucuronide (M3) [7,9]. Although the glucuronides show little affinity for the estrogen receptors and for bone tissue, they are important because they can be readily reconverted back into active raloxifene in various organs by β-glucuronidases residing in the liver, lung, spleen, kidney, bone and uterus [10].…”
Section: Discussionmentioning
confidence: 99%
“…According to the estimations, the fraction of raloxifene absorbed is high, 60 %, but only 2% reaches the systemic circulation in unconjugated form due to the high metabolic turnover during absorption [7]. The rest represents raloxifene conjugated by UDP-glucuronosyltransferases (UGTs) to raloxifene-4'-β-glucuronide (M2), raloxifene-6-β-glucuronide (M1) [7,8] and raloxifene-6,4'-diglucuronide 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 5 shown that raloxifene is probably transported by Pgp [11,12] while the corresponding glucuronides utilize the MRPs and organic anion transporter(s) (OAT) for their transport [12].…”
Section: Introductionmentioning
confidence: 99%